THE EFFECT OF ISOLATE SOY PROTEIN FORTIFICATION (Glycin max) FOR THE QUALITY OF CARP FISH BALLS (Osphronemus gouramy) - Axel Celvin Viralta; Desmelati Desmelati; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis research aimed to determine the effect of isolate soy protein fortification for quality of carp fishballs. Method used in this study was the experiment method, by processing carp fishballs with addition of isolate soy protein. The design used in this experiment was a nonfactorial completely randomized design (CRD),  which was an addition of isolate soy protein from weight of carp fish meat which consisting with 4 levels: B0 (without addition  isolate soy protein), B1 (addition 11% of isolate soy protein), B2 (addition 16% of isolate soy protein) and B3 (addition 21% of isolate soy protein). The parameters  tested in this experiment were organoleptic and proximate analysis. The result on organoleptic analysis based on the test levels showed that addition 100g (B3) of  isolate soy protein in carp fishballs was the best treatment, with average value score of appearance 7, with criteria of bright yellow, flavor value 6.92; the distinctive flavor of carp fishballs and strong isolate soy protein, taste value 6.76; with criteria very tasty and distinctive taste of carp and isolate soy protein, texture value 7.11; with compact and elasticity criteria. Based on proximate analysis, the value of moisture, protein, fat, and ash was 63.29%; 22.40%; 0.63%; and 2.46 respectively. Keywords: Carp Fish, Fishballs, Isolate Soy Protein